Responsabilidad del distrito frente a los accidentes de tránsito provocados por el SITP (2016)
With this research work is to make known to the victims of traffic accidents caused by the integrated public transport SIPT system, tools that allow them access to full compensation for damages caused, since they can learn an analysis of the best legal options to claim their rights and require compensation for damages. It is also necessary to analyze the causes of the frequent accidents of buses and the importance of implementing preventive actions, since they are empty address the issue, which expose citizens and / or users of SITP to risky circumstances, so it is necessary to raise responsibilities and understand from the administrative law implications of an administrative complaint, his times, stages and the prospects of success. In the case of drivers of SITP buses, there is the application of risk theory, in these cases has the effect of warning drivers, to the extent that they are creating a dangerous situation, must answer for any damage they cause; they have no right to run over a pedestrian simply because this goes through when the light does not allow it or because it does carelessly or intoxicated; the simple proof of the absence of fault or had acted diligently will not exonerate them from responsibility. A day in Bogota, on average, six accidents occur related to vehicles TransMilenio Mass Transit System, including articulated and feeders; and the Integrated Public Transport System (PSIS), blues and oranges. In addition, the figures continue to increase mortality, physical harm to persons and damage to infrastructure. Concessions are punctually, who face judicial proceedings that could compromise the system. That is, TransMilenio S.A. It does not assume direct responsibility for accidents caused and now is linked only as a defendant in 38 proceedings for direct reparation and seven criminal complaints. Finally we conclude in the development of this investigation that constitutional, legal and jurisprudential victims of traffic accidents caused by the Integrated Public Transport System - SITP can access to compensation for damage caused by the administrative procedure, through the action of direct repair mechanism that forces the state repair time by an act or omission has caused damage, damage that was caused by the exercise of an activity classified as dangerous, so it could declare responsible the Colombian State head of the Capital District and / or transport company Third Millennium TRANSMILENIO SA, corporation commercial nature with public contributions who is the manager of the System entity, the entity responsible for coordinating the different actors, plan, manage and control the provision of public service of urban mass transit, and is responsible for the efficient and continuous service delivery.